Bismuth as efficient sintering aid for TiO2-based low temperature dye sensitized solar cell - Hazim, Khir; Pandey, Adarsh Kumar; Saidur, Rahman Md; Muhammad Shakeel, Ahmad; Samykano, Mahendran; Nasrudin, Abd Rahim (Elsevier Ltd, 2024)
Flexible dye sensitized solar cell (DSSC) developed at low temperature with low conversion efficiency due to the poor interparticle contact and charge transfer has limited their further development. In this research, bismuth (Bi) nanoparticles were implemented as titanium dioxide (TiO2) photoanode sintering aid to combat this issue. By utilising the liquid phase sintering theory, interparticle contact of photoanode was improved due to neck formation at the TiO2–Bi matrix. This feat was achieved even at low temperature (150 °C and 200 °C) because Bi have a low melting point of 271.5 °C. The charge transfer was also found to have increased while the resistance lowered with the implementation of Bi from the plasmonic effects of Bi nanoparticles. The highest conversion efficiency was obtained at 7.93 % for the TiO2-5wt% Bi sample sintered at 200 °C. The efficiency was 2%–16 % higher than controlled DSSC samples prepared at high temperature (450 °C). The improvement in interparticle contact due to neck formation and enhanced charge transfer with reduced recombination reactions was attributed as the reason for the superior performance. Increasing the Bi composition even further caused reduction in the efficiency due to layer cracking and electron trapping sites from high amount of Bi.